Investigation of the Sound Source Regions in Open and Closed Organ Pipes - HRUŠKA, Viktor; DLASK, Pavel (Archives of Acoustics, 2019)
The airflow in the mouth of an open and closed flue organ pipe of corresponding geometrical proportions is studied. The phase locked particle image velocimetry with subsequent analysis by the biorthogonal decomposition is employed in order to compare the flow mechanisms and related features. The most significant differences lie in the mean velocity distribution and rapidity of the jet lateral motion. Remarks on the pressure estimation from PIV data and its importance for the aeroacoustic source terms are made and a specific example is discussed.